2007
DOI: 10.1111/j.1471-4159.2007.05165.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell death pathway that is partially caspase dependent, but morphologically non‐apoptotic, elicited by proteasomal inhibition of rat sympathetic neurons

Abstract: Proteasomal dysfunction has been linked to neurodegeneration. Pharmacological proteasomal inhibitors may have pro‐survival or pro‐death effects in neuronal cells. We have previously found that application of such agents to mouse sympathetic neurons leads to activation of the intrinsic apoptotic pathway. We show here that in rat sympathetic neurons proteasomal inhibition leads to a form of death that is morphologically non‐apoptotic, with features of autophagy. The intrinsic apoptotic pathway is activated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…We have recently shown (Lang‐Rollin et al. 2008) that in rat sympathetic neurons proteasomal inhibition leads to a form of death that is morphologically non‐apoptotic, but shows a number of the biochemical features of apoptosis, such as activation of the mitochondrial apoptotic pathway, resembling thus the form of death described here following WT ASYN over‐expression.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…We have recently shown (Lang‐Rollin et al. 2008) that in rat sympathetic neurons proteasomal inhibition leads to a form of death that is morphologically non‐apoptotic, but shows a number of the biochemical features of apoptosis, such as activation of the mitochondrial apoptotic pathway, resembling thus the form of death described here following WT ASYN over‐expression.…”
Section: Resultsmentioning
confidence: 56%
“…It is interesting to note that the death pathway described herein bears resemblance to a pathway we recently characterized in rat sympathetic neurons exposed to proteasomal inhibitors. In that setting as well, the intrinsic apoptotic pathway appeared to be activated, but then blocked at a point downstream of the mitochondria, leading to a morphologically non‐apoptotic form of death (Lang‐Rollin et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, under similar conditions, rat SCG neurons may survive NGF deprivation during acute withdrawal (Sadoul et al, 1996) but ultimately die nonapoptotically (with some apoptotic features) (Lang-Rollin et al, 2008). In our hands, Q97 expression did not reproduce all the effects of proteasome inhibition because Lang- Rollin et al (2008) found that CsA had no protective effect on proteasome-inhibition-mediated death, whereas we found that Q97-mediated cyt c release was delayed by treatment with cyclosporine A. Hence, Q97 causes additional signals in SCG neurons.…”
Section: Discussionmentioning
confidence: 63%
“…4c). To evaluate the possibility that mutant 19S subunits may induce morphologically non‐apoptotic death, as can occur in certain settings following pharmacological proteasome inhibition (Lang‐Rollin et al. 2008), we also assessed cell death more globally, by incorporation of the dye ethidium homodimer.…”
Section: Resultsmentioning
confidence: 99%